From waste paper basket to solid state and Li-HEC ultracapacitor electrodes: a value added journey for shredded office paper - Puthusseri, Dhanya; Aravindan, Vanchiappan; Anothumakkool, Bihag; Kurungot, Sreekumar; Madhavi, Srinivasan; Ogale, Satishchandra (Small, 2014)
Hydrothermal processing followed by controlled pyrolysis of used white office paper (a globally collectable shredded paper waste) are performed to obtain high surface area carbon with hierarchical pore size distribution. The BET specific surface area of such carbon is 2341 m 2 g(-1). The interconnected macroporous structure along with the concurrent presence of mesopores and micropores makes the material ideal for ultracapacitor application. Such waste paper derived carbon (WPC) shows remarkable performance in all solid-state supercapacitor fabricated with ionic liquid-polymer gel electrolyte. At room temperature, the material exhibits a power density of 19 000 W kg(-1) with an energy capability of 31 Wh kg(-1). The Li-ion electrochemical capacitor constructed using WPC as cathode also shows an excellent energy storage capacity of 61 Wh kg(-1)